2010
DOI: 10.1038/nrm2832
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of chromosome behaviour during mitosis

Abstract: For over a century, scientists have strived to understand the mechanisms that govern the accurate segregation of chromosomes during mitosis. The most intriguing feature of this process, which is particularly prominent in higher eukaryotes, is the complex behaviour exhibited by the chromosomes. This behaviour is based on specific and highly regulated interactions between the chromosomes and spindle microtubules. Recent discoveries, enabled by high-resolution imaging combined with the various genetic, molecular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
186
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(191 citation statements)
references
References 135 publications
(132 reference statements)
5
186
0
Order By: Relevance
“…Importantly, we have found that also wild-type MII oocytes frequently display merotelic attachments at the metaphase stage, as well as lagging chromosomes at anaphase onset. This strongly suggests that merotelic attachments contribute significantly to chromosome mis-segregation in wild-type female germ cells, similar to what previously been documented for somatic cells during mitosis 10,11,27 . In conclusion, our results show that merotely contributes to aneuploidy in mammalian oocytes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Importantly, we have found that also wild-type MII oocytes frequently display merotelic attachments at the metaphase stage, as well as lagging chromosomes at anaphase onset. This strongly suggests that merotelic attachments contribute significantly to chromosome mis-segregation in wild-type female germ cells, similar to what previously been documented for somatic cells during mitosis 10,11,27 . In conclusion, our results show that merotely contributes to aneuploidy in mammalian oocytes.…”
Section: Discussionsupporting
confidence: 87%
“…We found that chromosomes at the spindle equator displayed an amphitelic configuration (Fig. 1e), a geometric orientation promoted by opposing end-on microtubule attachments to the sister kinetochores of chromosomes [10][11][12] . Occasionally, one of the two sister kinetochores of chromosomes were bi-directionally attached to microtubules, suggesting also the presence of merotelic attachments ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 87%
“…2b). Lack of chromosome pulling/pushing forces by end-onattached microtubules to bi-oriented kinetochores 19 , which keeps chromosomes around the spindle equator, may explain the inefficiency of this partial and transient congression. It may also be explained by the reduction of microtubule density in the middle of the spindle, due to lack of microtubule stabilization by end-on attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Chromosome movement toward the spindle equator is initiated immediately after nuclear envelope breakdown (NEB) in prometaphase and is known as chromosome congression. 1,2 Chromosome movements during congression are driven by 2 main mechanisms: microtubule polymerization/depolymerization-based motion 3 and motor-dependent transport along microtubules. [4][5][6] The latter is mainly achieved through the coordinated activities of cytoplasmic Dynein, CENP-E and chromokinesins.…”
Section: Introductionmentioning
confidence: 99%